1995
DOI: 10.1002/cbf.290130108
|View full text |Cite
|
Sign up to set email alerts
|

Platelet glycohydrolase activities: Characterization and release

Abstract: Granules containing acid hydrolases have been detected in human platelets but have not been thoroughly characterized. We have studied the activity and characteristics of glycohydrolases present in normal human platelets, evaluated their release upon stimulation with thrombin, and assessed the contribution of platelet - released lysosomal contents to the glycohydrolase activity present in normal serum. Platelets contained a remarkable glycohydrolase activity with a prevalence of beta - N-acetylhexosaminidase. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
(2 reference statements)
3
13
0
Order By: Relevance
“…One of the most consistent defects so far reported is the reduction in the content and release of and granules, in part due to an in vivo leakage (platelet 'exhaustion') [15][16][17][18]. Human platelets contain and release in vivo upon activation, besides -and -granules, also -granules [26], which store lysosomal enzymes, particularly acid glycohydrolases, the most abundant of which is Hex [25]. No studies have previously examined whether the platelet Hex content and in vivo release is altered in MPD patients.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…One of the most consistent defects so far reported is the reduction in the content and release of and granules, in part due to an in vivo leakage (platelet 'exhaustion') [15][16][17][18]. Human platelets contain and release in vivo upon activation, besides -and -granules, also -granules [26], which store lysosomal enzymes, particularly acid glycohydrolases, the most abundant of which is Hex [25]. No studies have previously examined whether the platelet Hex content and in vivo release is altered in MPD patients.…”
Section: Discussionmentioning
confidence: 96%
“…DEAE-cellulose chromatography was performed as previously described [25,32] using a 1-ml column equilibrated with 10 mM sodium phosphate buffer, pH 6.0. Enzymatic activity retained by the column was eluted in a linear gradient of NaCl that reached a concentration of 0.5 M in 20 ml of buffer, then washed with 5 ml of 1 M NaCl.…”
Section: Deae-cellulose Chromatographymentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, these authors find significantly higher ß-7V-acetylhexosaminidase activity in serum than in plasma, and suggest that the release of enzyme from the platelets could occur during coagulation. Recently, Emiliani et al (33) have demonstrated that stimulation with thrombin provokes a release by platelets of ß-Af-acetylhexosaminidase and other glycohydrolases.…”
Section: Discussionmentioning
confidence: 99%